Experience capitalization to scale up innovations and good practices in Mali - Coulibaly, Modibo (Technical Centre for Agricultural and Rural Cooperation, 2019)
The Forum des Services de Conseil Agricole et Rural du Mali (FOSCAR-Mali) has adopted the experience capitalization approach, linking it to the production of radio programmes and videos. Produced in a participatory manner, these involve various stakeholders linked to the rice value chains